In vivo effects of aflatoxin B1 and benzo[a]pyrene on the heart muscle of chicken embryos. Issue 14 (6th December 2021) - Knížatová, Nikola; Massányi, Martin; Kołodziejczyk, Łukasz M.; Kováčik, Anton; Tokárová, Katarína; Greń, Agnieszka; Binkowski, Łukasz J.; Formicki, Grzegorz; Capcarová, Marcela; Massányi, Peter; Lukáč, Norbert
Abstract: The purpose of the present study was to evaluate the effects of aflatoxin B1 (AFB1) and benzo[a]pyrene (BaP) on the heart muscle of chicken embryos of the broiler line Ross 308. The benzo[a]pyrene in the organic oil solution was injected in ovo on the 6th day of the incubation in doses of: 0.1, 0.5, and 1 mg/kg weight of eggs; the aflatoxin B1 in the organic oil solution was injected in ovo on the 6th day of the incubation into the yolk in doses of 80, 120 and 240 ng/kg weight of eggs. Multiple biochemical and hepatic parameters have been observed, including sodium, potassium, chloride, cholesterol, uric acid, total proteins, aminotransferase aspartate, and aminotransferase alanine. A low dose of AFB1 and BaP administered in ovo during early embryonic development had a significant impact on chicken embryonic development, as demonstrated by alterations in biochemical, mineral, and hepatic parameters.